2000
DOI: 10.1007/pl00000689
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of alcohols and their protein binding sites

Abstract: Alcohols affect a wide array of biological processes including protein folding, neurotransmission and immune responses. It is becoming clear that many of these effects are mediated by direct binding to proteins such as neurotransmitter receptors and signaling molecules. This review summarizes the unique chemical properties of alcohols which contribute to their biological effects. It is concluded that alcohols act mainly as hydrogen bond donors whose binding to the polypeptide chain is stabilized by hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 83 publications
7
66
1
Order By: Relevance
“…For example, in firefly luciferase, one of the binding pockets for the anesthetic bromoform includes histidine, arginine, threonine, and two glutamic acids (5). Our results are in partial agreement with a recent analysis that concluded that alcohol binding sites possess a hydrogen bond acceptor in a turn or loop often located near the Nterminal end of an ␣-helix (35). The location of anesthetic sites at the interface between two structural domains has been noted in some other cases (6,36) and may prove to be a common motif for general anesthetic binding sites.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in firefly luciferase, one of the binding pockets for the anesthetic bromoform includes histidine, arginine, threonine, and two glutamic acids (5). Our results are in partial agreement with a recent analysis that concluded that alcohol binding sites possess a hydrogen bond acceptor in a turn or loop often located near the Nterminal end of an ␣-helix (35). The location of anesthetic sites at the interface between two structural domains has been noted in some other cases (6,36) and may prove to be a common motif for general anesthetic binding sites.…”
Section: Discussionsupporting
confidence: 92%
“…This mode of alcohol binding is unrelated to the non-enzymatic sites that occur in alcohol-sensitive ion-channels. Information from an analysis of protein crystal structures solved using alcohols as cosolvents revealed that H-bonds between the alcohol and protein are formed predominantly with atoms in the protein backbone 18 . These are non-specific interactions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A blood alcohol level of 0.1%, the legal limit for driving in many US states, corresponds to a concentration of ~22 mM. Structural and biophysical studies of anesthetics bound to model proteins have defined the importance of both non-polar and polar groups in the binding sites of these molecules [19][20][21][22][23] and binding sites for alcohols will also posses such an amphipathic nature 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies are consistent with the presence of physically circumscribed hydrophobic protein cavities that constitute the alcohol and general anesthetic sites. Also, studies with soluble model proteins have examined the relationship between anesthetic solubility and anesthetic action along with structure-function analysis and thermodynamic arguments and suggest that polar interactions also contribute to the binding of alcohol and inhaled anesthetics (5,9,(12)(13)(14)(15). Polar interactions are also likely to contribute to the binding of general anesthetic agents to ion channels, which are critical physiological targets of these agents (including 1-alkanols).…”
mentioning
confidence: 99%